Teacher professionalism development in Indonesia about environmental literacy - H. Husamah; Tutut Indria Permana; Yanur Setyaningrum; Abdulkadir Rahardjanto; Samsun Hadi (Universitas Muhammadiyah Malang, 2025)
The professionalism of teachers in Indonesia is being reshaped by two main agendas: strengthening Continuing Professional Development (CPD), and integrating environmental literacy to address ecological challenges. This article examines the operationalization of Teacher Professionalism Development (TPD) through certification, structured CPD, and the Guru Penggerak (Teacher Mobilizer) program, while analyzing why environmental literacy—despite being supported by policies such as the Adiwiyata Program and its successor, the School Environmental Care and Culture Movement (Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah/GPBLHS)—remains unevenly integrated into classroom practice. Based on a review, four critical points are synthesized: (1) the gap in translating policy into practice, (2) the need for pedagogical content knowledge on sustainability, (3) collaborative and self-directed learning models for teachers (e.g., Teacher Professional Development Tasks based on heutagogy or self-determined learning), and (4) the need for a coherent assessment and incentive system for environmental literacy outcomes. As a practical pathway, it is proposed to align CPD mechanisms with environmental literacy competencies, connect the